Tinjauan Ekonomi Islam: Pengaruh Foreign Direct Invesment dan Nilai Tukar Terhadap Produk Domestik Bruto di Kawasan Asean - Nur Aini Dwiyanti; Ghina Ulfah Saefurrohman; Alief Rakhman Setyanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of Foreign DirectInvestment (FDI) and exchange rates on Gross Domestic Product (GDP) in theASEAN region from an Islamic economic perspective for the period 2014-2024. ASEANis a dynamic region with rapid economic growth, but itfaces significant challenges influenced by foreign investment flows andexchange rate fluctuations. This study uses a quantitative approach with time series and cross-section secondary data in the form of dynamic panel data, as well as usingthe dynamic panel regression analysis method using the FD-GMM model. The data was obtainedfrom the World Bank and ASEAN Statistics. The results show that FDIhas a positive and significant effect on GDP, reinforcing that foreign investmentcan drive economic growth through increased capital, technology transfer, and job creation. Conversely, exchange rates do nothave a significant effect on GDP in the tested data. From an Islamic economic perspective, investment and exchange rates must be carried out in accordance with sharia principlessharia principles in order to provide blessings and benefits. Therefore, in conclusion,an increase in FDI can be a major driver of GDP growth in ASEAN, whileexchange rates need to be managed in a stable manner so as not to cause negative impacts.This study makes an important contribution to economic policy-makingin ASEAN within the framework of sharia for sustainable economic development.